1993
DOI: 10.1111/j.1365-2818.1993.tb03313.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of co‐localization of objects in dual‐colour confocal images

Abstract: memory arrays (Dean et al.. 1990). a dual-colour image.A method to measure the degree of co-localization of objects in confocal dual-colour images has been developed. This image analysis produced two coefficients that represent the fraction of co-localizing objects in each component of a dual-channel image. The generation of test objects with a Gaussian intensity distribution, at well-defined positions in both components of dual-channel images, allowed an accurate investigation of the reliability of the proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
1,865
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,910 publications
(1,894 citation statements)
references
References 18 publications
27
1,865
0
2
Order By: Relevance
“…Value of 1 represents perfect correlation, 0 means no correlation. 42,43 It has been reported that R p around 0.91 indicates that two images are almost identical, 44 and R p around 0.75 shows a relatively high degree of co-localization. 45 Tube formation assay.…”
Section: Methodsmentioning
confidence: 99%
“…Value of 1 represents perfect correlation, 0 means no correlation. 42,43 It has been reported that R p around 0.91 indicates that two images are almost identical, 44 and R p around 0.75 shows a relatively high degree of co-localization. 45 Tube formation assay.…”
Section: Methodsmentioning
confidence: 99%
“…This region of interest was defined by manual segmentation of the platelets and collagen fibres using the interference reflectance channel. The Manders’ coefficients (M1 and M2) were used as the co-localisation measure [39]. …”
Section: Methodsmentioning
confidence: 99%
“…55 Colocalization coefficients ranging from 0 (none of the signal above threshold in that channel exists as colocalized with the other channel) to 1 (all of the signal above threshold in that channel exists as colocalized with the other channel) for each of the selected objects were then obtained. A colocalization coefficient of 0.5 or higher was considered to be indicative of colocalization.…”
Section: ■ Methodsmentioning
confidence: 99%